National day family : a study of the Singaporean family as depicted in national day music videos. - Shahul Hameed. (2012)
My Graduation Project aims to explore how the Singapore family is depicted in its annual National Day music videos. I start off by investigating the media landscape of Singapore and look for instances where the state regulates and produces media that is in line with its larger political discourse. Thereafter, I will at the National Day music videos in question, from the years 2007 to 2011, and isolate the scenes where a family appears. Using stills from these scenes, I will do a textual analysis for the signifier and the signified elements in the videos. With this, I put forth the denotative and connotative meanings behind these scenes. Upon this analysis, I argue that a happy family as seen in the videos is one that fits the state’s definition of a ‘proper’ family. This definition consists of a heterosexual couple with children. Also, I point out that single parents, when appearing, are not reflected in the similar positive light as the ‘proper’ families are in the videos. I draw parallels with this finding and the state’s obvious displeasure towards single parents as seen through the parent’s disqualifications from benefits and reliefs available to parents who are still together. Lastly, I argue that even though foreign domestic workers perform most of the traditional familial duties and are seen with their employer’s families very frequently in reality today, their blatant exclusion from all the music videos is a part of the state’s aim to preserve the ideology of the Singapore family being a self-sustaining basic unit of society entrenched in ‘Asian Values’. This only further reiterates the notion that the portrayals of the family in these videos are largely designed to perpetuate the state’s discourse on the Singaporean family.